CERAMAH DESAIN BERBASISKAN KECERDASAN VISUAL - Pranata, Moeljadi (Institute of Research and Community Outreach - Petra Christian University, 2003)
Articulate intrinsic values is necessary for further progress to be made in design instruction. The main inter-related areas in which such values is the language media of design and the modes of thought which relate particulary to desaign abilities. Many theories indicate that tought is progessec externalized and directed by acquisition of a suitable language medium. Media appropriate to the progression and development of the style of thought might therefore be looked upon a essential means for the encouragement of learning and instruction. Abstract in Bahasa Indonesia : Artikulasi nilai intrinsik sangat penting bagi peningkatan pembelajaran desain. Area utama yang berhubungan dengan nilai tersebut ialah media bahasa desain dan mode pemikiran yang berhubungan dengan kemampuan desain. Beberapa teori telah menunjukkan bahwa pemikiran manusia telah dieksternalkan dan diarahkan melalui akuisisi medium bahasa yang sesuai. Media yang tepat pada kemajuan dan pengembangan gaya pemikiran dipandang sebagai sarana penting untuk mendorong belajar dan pembelajaran. visual intelligence%2C design education%2C instructional method.